The importance of the coach in predicting implicit beliefs about skill and beliefs about the causes of success in handball players - Gómez-López, M.; Manzano-Sánchez, D.; Merino-Barrero, J. A.; Valero-Valenzuela, A. (International Journal of Environmental Research and Public Health, 2019)
The objective of the present study was to determine the predictive capacity of the motivational climate generated by coaches and perceived by handball players on implicit beliefs about ability and beliefs about the causes of success in sport. The sample consisted of 444 youth handball players. These players completed the Beliefs about the Causes of Success in Sport Questionnaire, the Conceptions of the Nature of Athletic Ability Questionnaire, Version Two, and the Perceived Motivational Climate in Sport Questionnaire. The structural regression model showed that the mastery climate positively predicted the belief in incremental ability and that this in turn positively predicts both belief in athletic success through effort and ability. The results reflected the importance of the coach in the formative process of the player and the search for performance in sport.